Infrastrukturen des Verkehrs im deutschsprachigen Raum (18. und frühes 19. Jahrhundert): Ein Forschungsüberblick in revisionistischer Perspektive - Stefan Brakensiek (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– Around 1800, transport infrastructure in Germany was based on traditional roads and waterways. The fundamental changes that were heralded in England and France in the course of the 18th century were hindered by the political situation. This article focuses on the question of whether there were other reasons for the long survival of traditional structures besides political fragmentation. A twofold hypothesis will be examined: It is possible that traditional roads and waterways were more efficient than claimed by historical research? We thus suggest, firstly, that the main reason for their efficiency was the efforts of providers and users to make them more flexible. Secondly, some political difficulties were overcome by coordinating the activities of various imperial estates.
Keywords: N73; 330; Infrastructure; Roads; Canals; Political coordination of innovations